Numerical model of variable valve timing distribution for a supercharged diesel engine - Benallal, Abdellah; Hayyani, Mohamed Yasser; Mhadhbi, Ghazi; Ilinca, Adrian (Institute of Advanced Engineering and Science, 2024)
Recently, there's been a strong drive to improve performance of diesel engines while reducing their greenhouse gases emissions. Techniques like exhaust gas recirculation, turbocharging, and variable valve timing have become widespread. The last technique fine-tunes valve operation based on engine speed, which optimize efficiency and power output while saving fuel. This study zeroes in on a specific 4-cylinder, 4-stroke diesel engine of 1.56-liter, GT-Power software is employed to examine a supercharged version and implementing diverse valve lift techniques. The findings are revealing a substantial 30% increase in power output. At 1000 rpm, power rises from 15.1 kW for the standard engine to 19.72 kW for the modified version. For higher engine speeds, the improvements become even more pronounced, reaching a 66% boost compared to the standard configuration. Furthermore, the newly configured engine showcases an impressive 13% decrease in fuel-specific consumption at elevated engine speeds, contributing to enhanced technical performance and fuel efficiency. The numerical model developed in this study holds the potential to aid in the design of novel diesel engines equipped with variable valve timing systems. To lend further support to these findings, experimental validation is recommended.